Mucocutaneous Horn in Dog - de Araújo, Joyce Maíra; de Lima, Stephanie Carrelo; Rondon, Eric Schmidt (Acta Scientiae Veterinariae, 2020)
Background: Cutaneous horn is a circumscribed exophytic lesion composed of dense, compact keratin with hyperplastic epidermis, which is primarily orthokeratotic and may include foci of parakeratosis. The hyperkeratotic protuberance resembles a horn but lack bone. In humans, it is well-documented with a wide range of primary epidermal lesions identified. In dogs, the reports are rare and brief. The diagnosis is based on its appearance and excisional biopsy reveals the triggering lesion. The objective of the present work is to describe the clinical presentation, predictive benignancy finds, treatment and follow-up of a case of cutaneous horns that arose from anal mucocutaneous boundary in a dog. Case: A 6-month-old male Pug presented two tumors in the anus noted in the early months of life. Complete blood count, serum chemistry profile, surgery, histopathological analysis and postoperative outcome were performed. Possible relapses were follow-up until 11 months after surgery. On physical examination, the dog was otherwise healthy. The two horn-like tumors were protruding from the mucocutaneous junction of the external anal sphincter in a sun-protected area. Both were higher than wide in base or, in other words, they had a high height-to-base ratio. During surgery, the masses were excised using an electronic scalpel and sent to histopathological analysis. The post-operative care consisted of cephalexin and meloxicam prescriptions. Also, it was recommended 0.9% NaCl solution wound flushing followed by topical chlorhexidine digluconate solution (1%) whenever dirt or defecation were noticed. The surgical wound healed after two weeks by second intention. Histopathology found well-delimited masses that covers the epidermis and dermis and displaces the cutaneous appendages towards the underlying musculature with an aggregate of lymphoplasmohistiocytic inflammatory infiltrate in the adjacent dermis. These finds and the presence of orthokeratotic hyperkeratosis and epidermis hyperplasia confirmed the clinical diagnosis of cutaneous horns. There were no signs of malignance. After surgery, no relapse occurred. Discussion: To the best of the authors’ knowledge, this is the first confirmed case of cutaneous horns in mucocutaneous junction. Furthermore, the tumors were found in a region with little exposure to sunlight which is unusual. The tumor’s narrow bases and the absence of continuous and dense inflammatory infiltrate shown to be predictive of benignancy as occurs in human beings. During surgical planning, it was decided not to establish wide margins around the masses. The decision considered the morphological signs of benignancy of the tumors described for human beings as no surveys about prevalence of benignity or malignancy associated with cutaneous horns were found in dogs. In addition, a more extensive excision could promote anal sphincter dysfunction. There was no tumors recurrence suggesting that the primary underlying lesions have been healed and confirming that predictive benignancy morphological characteristics applied in human patients can be useful for small animals. Veterinary clinicians and surgeons must be in constant vigil of cutaneous horns uncommon presentations and report them to create a solid database that can be useful for prognosis and surgical planning. The morphological predictive factors can be applied to avoid unnecessary extensive surgical excisions that could lead to functional or cosmetic impairment.